PEMINDAHAN TANAH WAKAF DI DESA SUKAMULIA KABUPATEN LOMBOK TIMUR DITINJAU DARI HUKUM ISLAM - Zikri, Sri nirwana Sarowati (al-Hikmah : Jurnal Studi Islam, 2022)
One of the problems that has occurred among the community is the transfer of waqf land or land. The purpose of this study was to determine the transfer of waqf land according to Islamic law.  This type of research uses library research with primary, secondary and tertiary data sources.  This research shows that the transfer of waqf land according to Islamic law cannot be transferred for any reason. Waqf assets cannot be used as collateral, confiscated, handed over for sale, inherited, changed, and transferred in the form of transfer of rights except at the request of the waqif and the Waqf Board with the aim of mutual benefit.